2020
DOI: 10.2188/jea.je20180193
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Fasting Blood Glucose Levels Are Associated With Lower Cognitive Function, With a Threshold in Non-Diabetic Individuals: A Population-Based Study

Abstract: Background: Cognitive dysfunction has been recognized as a diabetes-related complication. Whether hyperglycemia or elevated fasting glucose are associated with cognitive decline remains controversial. We aimed to investigate the relationship between fasting glucose levels and cognitive function in diabetic and non-diabetic individuals. Methods: Participants were Japanese diabetic (n = 191) and non-diabetic (n = 616) men, aged 46-81 years, from 2010-2014. Blood samples were taken after a 12 h fast. The Cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(40 reference statements)
1
3
0
2
Order By: Relevance
“…The linear association was independent of potential confounders including socio-demographics, health behaviors, and adiposity. Our findings corroborate results from several previous epidemiological studies showing dose-response relationships between fasting or postprandial blood glucose levels and cognitive deficits in non-diabetic elderly adults ( 5 7 ). The persistent adverse impact of elevated glucose on cognition across the spectrum highlights the need for early screening and preventive interventions even before the diagnosis of diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The linear association was independent of potential confounders including socio-demographics, health behaviors, and adiposity. Our findings corroborate results from several previous epidemiological studies showing dose-response relationships between fasting or postprandial blood glucose levels and cognitive deficits in non-diabetic elderly adults ( 5 7 ). The persistent adverse impact of elevated glucose on cognition across the spectrum highlights the need for early screening and preventive interventions even before the diagnosis of diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous epidemiological studies have demonstrated that diabetes mellitus is one of the key risk factors for cognitive decline (2)(3)(4). Moreover, increased blood glucose levels are thought to be associated with cognitive impairment even among people without diabetes (5)(6)(7). For example, a prospective study found that a reverse U-shaped relationship was observed between fasting glucose and cognitive function, identifying a threshold for highest cognitive performance at 3.97-6.20 mmol/L fasting glucose (5)., indicating impaired fasting glucose may be associated with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Peningkatan kadar gula darah puasa sering diasosiasikan dengan penurunan fungsi kognitif dan dapat menjadi salah marker dalam menilai gangguan fungsi kognitif. 13 Pada kondisi normal masuknya glukosa ke dalam sel diatur oleh insulin dan kecepatan transpor glukosa melalui suatu protein spesifik yang berikatan pada membran plasma yaitu glukosa tranpsorter (GLUT). GLUT sebagai protein transporter yang sudah diketahui dan dikenal dengan baik sebagai transporter glukosa adalah bentuk GLUT 1 sampai GLUT 14.…”
Section: Pendahuluanunclassified
“…Mengingat kontrol kadar gula darah puasa yang normal sangat penting bagi tubuh dan peningkatan peningkatan kadar gula darah puasa dikaitkan dengan gangguan fungsi kognitif dan menjadi marker dalam menilai gangguan fungsi kognitif. 13 Serta satu penelitian menunjukkan ekspresi GLUT4 menurun pada kondisi terjadinya peningkatan kadar gula darah puasa pada penyakit DM. 17 Berdasarkan latar belakang yang diuraikan peneliti bertujuan untuk mengetahui pengaruh kadar gula darah puasa terhadap ekspresi GLUT4 neuron hipokampus pada tikus model diabetes yang diinduksi STZ dan NA.…”
Section: Pendahuluanunclassified